Urbanization drives cross‐taxon declines in abundance and diversity at multiple spatial scales. (1st January 2020) - Piano, Elena; Souffreau, Caroline; Merckx, Thomas; Baardsen, Lisa F.; Backeljau, Thierry; Bonte, Dries; Brans, Kristien I.; Cours, Marie; Dahirel, Maxime; Debortoli, Nicolas; Decaestecker, Ellen; De Wolf, Katrien; et al.
Abstract: The increasing urbanization process is hypothesized to drastically alter (semi‐)natural environments with a concomitant major decline in species abundance and diversity. Yet, studies on this effect of urbanization, and the spatial scale at which it acts, are at present inconclusive due to the large heterogeneity in taxonomic groups and spatial scales at which this relationship has been investigated among studies. Comprehensive studies analysing this relationship across multiple animal groups and at multiple spatial scales are rare, hampering the assessment of how biodiversity generally responds to urbanization. We studied aquatic (cladocerans), limno‐terrestrial (bdelloid rotifers) and terrestrial (butterflies, ground beetles, ground‐ and web spiders, macro‐moths, orthopterans and snails) invertebrate groups using a hierarchical spatial design, wherein three local‐scale (200 m × 200 m) urbanization levels were repeatedly sampled across three landscape‐scale (3 km × 3 km) urbanization levels. We tested for local and landscape urbanization effects on abundance and species richness of each group, whereby total richness was partitioned into the average richness of local communities and the richness due to variation among local communities. Abundances of the terrestrial active dispersers declined in response to local urbanization, with reductions up to 85% for butterflies, while passive dispersers did not show any clear trend. Species richness also declined with increasing levels of urbanization, but responses were highly heterogeneous among the different groups with respect to the richness component and the spatial scale at which urbanization impacts richness. Depending on the group, species richness declined due to biotic homogenization and/or local species loss. This resulted in an overall decrease in total richness across groups in urban areas. These results provide strong support to the general negative impact of urbanization on abundance and species richness within habitat patches and highlight the importance of considering multiple spatial scales and taxa to assess the impacts of urbanization on biodiversity. Abstract : We studied the effect of local‐ and landscape‐scale urbanization on the abundance and species richness of aquatic (cladocerans), limno‐terrestrial (rotifers) and terrestrial (butterflies, ground beetles, ground‐ and web spiders, macro‐moths, orthopterans and snails) invertebrate groups. Abundances of the terrestrial active dispersers declined, often dramatically, in response to local urbanization, while passive dispersers did not show any clear trend. Species richness also declined with increasing urbanization due to biotic homogenization and/or local species loss, but responses were highly heterogeneous in magnitude and spatial scale. Overall, these results strongly support the general negative impact of urbanization on species communities.